Racist Violence in Europe - Witte, Rob. author. aut Link
X, 261 p.
Keywords: All over Europe, asylum-seekers, immigrants and minorities are increasingly finding themselves under violent attack. Who are the perpetrators? What are their motives? To what extent are right-wing or neo-Nazi organizations involved? How do the authorities and the police respond? What are the roles of the media, the public opinion and anti-racist movements? What can be done to stop the violence? These are questions addressed in this volume by some of Europe's leading experts on racism and racist violence.